Land Status of The Community of Kampung Tua In Batam City After The Birth of Agrarian Law - Aurelia, Gina; Darmadi, Nanang Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Land registration in Batam only started in the 1990s. Land certification in the authority area began with the birth of the Management Rights (HPL) held by BP Batam.The exclusion of the existence of old villages in the formation of the Batam Authority, is evident in the granting of HPL to the Batam Authority by the Government as stated in the Decree of the Minister of Home Affairs No. 43 of 1977. The granting of HPL to the Batam Authority in this Decree is possible on locations that are not yet clear and clean, if there is community land that is still controlled/cultivated or owned with certain rights on the land area that has been issued with an HPL Decree, only given the option to receive compensation. The purpose of this study is to analyze: 1) a legal review of the status of land ownership of old villages in Batam City according to Agrarian Law. 2)Legal protection of land ownership rights in the Old Village community of Batam City after the Agrarian Law.This type of research is normative legal research. The approach method in this research iscase study approach and legislation approach. The type and source of data in this study are secondary data. Data analysis is an activity in research in the form of conducting a study of the results of data processing. The results of this study are According to Article 3 of the UUPA, there is a statement of recognition regarding the existence of customary rights of customary law communities as long as they still exist in reality, meaning that if in reality they do not exist, then the customary rights will not be revived, and no new customary rights will be created. Customary rights are allowed to continue to be regulated by each customary law community. Old villages, or customary law communities, have a special place in the UUPA (Basic Agrarian Law). The UUPA recognizes the existence of customary law communities and their customary rights, as long as they still exist and do not conflict with national interests.Keywords: Agrarian Law; Batam City; Land; Old Village.